A Decade of Reform in Latin America: Has it Delivered Lower Volatility? - Michael Gavin (Inter-American Development Bank, Office of the Chief Economist, 1997)
Have the economies of Latin America become less volatile as a result of the economic stabilization and structural reforms implemented during the past decade? The answer is a qualified yes. The reforms have helped, but more needs to be done to ensure the macroeconomic stability required for accelerated and more equitable long-run growth in the region. Structural reforms have helped reduce volatility, but volatility remains high by international standards and has not declined in all countries. The paper offers a policy agenda, raising questions for discussion in four key areas: (i) How can fiscal management be made more stabilizing? (ii) How can management of domestic financial markets contribute to lower economic volatility? (iii) How should capital flows be managed? (iv) What is the role of the exchange rate regime?
Keywords: 330